Case Report: Near-Fatal Intestinal Hemorrhage and Acute Acalculous Cholecystitis due to Vi-Negative and Fluoroquinolone-Insensitive Salmonella enterica Serovar Typhi Infection: A Rare Entity - Gong, Yuehua; Li, Jianlin; Zhu, Dongnan; Wang, Songsong; Xu, Yingchun; Li, Yan; Wang, Yanqing; Song, Yan; Liu, Wenjuan; Tian, Yunlong (Frontiers in Medicine, 2021)
Typhoid fever is usually a mild clinical disease. Typhoid fever with massive intestinal hemorrhage is rare in the antibiotic era. Acute acalculous cholecystitis (AAC) is also rare in adults. Here, we describe the first adult case of typhoid fever with both complications due to Vi-negative and fluoroquinolone-insensitive Salmonella enterica serovar Typhi (S. Typhi) infection. We aim to alert physicians to this rare condition.